Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s10439-012-0572-x
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Simulation Approach to Studying Anterior Cruciate Ligament Strains and Internal Forces Among Young Recreational Women Performing Valgus Inducing Stop-Jump Activities

Abstract: Anterior cruciate ligament (ACL) injuries are commonly incurred by recreational and professional women athletes during non-contact jumping maneuvers in sports like basketball and volleyball, where incidences of ACL injury is more frequent to females compared to males. What remains a numerical challenge is in vivo calculation of ACL strain and internal force. This study investigated effects of increasing stop-jump height on neuromuscular and bio-mechanical properties of knee and ACL, when performed by young fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 44 publications
(61 reference statements)
0
54
0
Order By: Relevance
“…plexities have been developed, either alongside cadaveric testing to extend the experimental results 23,[33][34][35][36] , or in combination with in vivo measurements of joint kinematics, external ground reaction forces and muscle-tendon forces to investigate the factors contributing to ACL loading during jump landing 11,[37][38][39][40][41] .…”
Section: @ C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 99%
See 4 more Smart Citations
“…plexities have been developed, either alongside cadaveric testing to extend the experimental results 23,[33][34][35][36] , or in combination with in vivo measurements of joint kinematics, external ground reaction forces and muscle-tendon forces to investigate the factors contributing to ACL loading during jump landing 11,[37][38][39][40][41] .…”
Section: @ C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 99%
“…This finding is in line with the in vitro results by Withrow et al 26 , who reported reduced peak AM-ACL strain with increased passive stiffness of the hamstrings, suggesting that greater hip flexion during landing may help to increase the muscles' force generating capacity to reduce anterior shear forces, and thus contribute to reduced ACL loading. Most computational models represented the ACL ligament as a straight-line 1D segment with pre-defined, non-linear elastic material properties with its insertion sites based on cadaveric measurements 11,23,[37][38][39] . In a computationally more involved approach, Kiapour et al 33 developed an anatomically-based Finite Element (FE) model of the knee joint based on CT/MRI images of one female athlete (25 years old).…”
Section: @ C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 99%
See 3 more Smart Citations